Structural characterisation of amorphous solid dispersions via metropolis matrix factorisation of pair distribution function data. Issue 89 (3rd October 2019) - Geddes, Harry S.; Blade, Helen; McCabe, James F.; Hughes, Leslie P.; Goodwin, Andrew L.
Abstract : We use total scattering and non-negative matrix factorisation to characterise the structure of an amorphous pharmaceutical in a complex mixture. Abstract : We measure the X-ray pair distribution functions (PDFs) of a series of felodipine:copovidone amorphous solid dispersions. Using a newly-developed Metropolis Matrix Factorisation (MMF) algorithm we extract from these data the PDF of the amorphous felodipine component in isolation. Our MMF analysis allows quantification of the degree of drug crystallinity in each sample, and structural characterisation of the amorphous drug via its PDF. Comparison with atomistic simulations reveals that the (in)accessibility of conformational rotamers distinguishes amorphous and crystalline felodipine, in turn suggesting design routes for stabilising the amorphous form. We discuss the conceptual importance of our results in the context of characterising not only amorphous pharmaceuticals, but complex mixtures in general.